PRODUKSI BIJI ARBILA (Phaseolus lunatus L.) SEBAGAI PAKAN AKIBAT LEVEL INOKULUM RIZOBIUM YANG BERBEDA - Bernadete Koten; Redempta Wea; Agustinus Semang (Partner, 2016)
The research aimed to evaluate the potential production of Arbila (Phaseolus lunatus L.) seed at different level of rizobium inoculants. This research has been conducted in Kupang State Agricultural Polytechnic during 4 months. The research was using randomized block design (RBD) having 5 treatments and 4 replications (20 units). The treatments were I1:  without inoculant, I2 :  10 g rizobium inoculant /kg seed, I3 : 20 g rizobium inoculant /kg seed, I4 : 30 g rizobium inoculant /kg seed, dan I5 : 40 g rizobium inoculant /kg seed. The observed variables were fresh seed production (ton/ha), dry weight seed production (ton/ha), weight of 100 seeds (g), and dry matter seed production (ton/ha). Data were analysed using variance analysis and continued with Duncan test. The result showed that the performance of Arbila seed were influenced by inoculant level. Increasing in inoculant level caused increasing in production of arbila seed. The higher seed production was the seed having 40 g rizobium inoculant /kg. The production were 3.62 tons of fresh seed/ha,  3.41 tons of dry seed/ha, 33.83 g per 100 seeds, 3.25 tons of DM /ha. This production was actually not different with seed having 30 g rizobium inoculant /kg seed.  The production were 2.57 tons of fresh seed/ha, 2.53 tons of dry seed/ha, 32.18 g per 100 seeds, and 2.42 tons of DM /ha. In conclusion, treatments with 40 g or 30 g of rizobium inoculant per kg seed were the best level for Arbila plant to produce higher seed. Key Words : Legume Arbila (Phaseolus lunatus L), Rizobium Inoculant, seed production, feed plant.